Features of supporting therapy of patients with generalized periodontitis - Попович, І. Ю.; Петрушанко, Т. О. (Actual Dentistry, 2019)
Actuality. Complex treatment of patients with generalized periodontitis involves the phase of treatment, the implementation of general therapy and a number of local interventions. The goal of curation tactics for patients with the specified pathology is to achieve stable remission, and in the long-term stabilization of periodontitis. A factor in the further prognosis of the disease is the implementation of maintenance therapy with simultaneous monitoring of patients. An important component of maintenance therapy is the prevention of local inflammation in periodontal tissues. The goal of our work was to evaluate the effectiveness of the use of the drug «Tantum Verde®» in patients with chronic generalized periodontitis at the stage of local supportive therapy. Materials and methods. Clinical and radiological monitoring for two years was performed in 50 patients with chronic generalized periodontitis of the 2-nd degree of severity, which were divided into two groups: control (used alcoholic solution of «Chlorophyllipt» during maintenance therapy) and experimental (used tablets of «Tantum Verde®» at the stage of supportive therapy). Results. Dynamic reserch during two-year testified to the effectiveness of the use of maintenance therapy at the stage after performing of oral hygiene of the oral cavity with «Tantum Verde®» in the form of tablets which dissolve in oral cavity. Patients of the experimental group on the second day after removal of dental deposits and use of the drug «Tantum Verde®» reported the disappearance of pain in the gums, swelling and gum bleeding. Conclusions. The results of clinical and radiological examination of patients indicate the feasibility of using the non-steroidal and anti-inflammatory drug «Tantum Verde®» in the form of tablets at the stage of local supportive treatment of patients with chronic generalized periodontitis. This drug has a complex effect due to the strong analgesic, anti-inflammatory and antimicrobial effects. Key words: supportive therapy, generalized periodontitis, «Tantum Verde®».